Possible methods of analysis of systems of hydraulic streams formation - Stas, С.В.; Shkarabura, Н.Г. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The physical and exairenergetic modelling of the system of formation of immobile and pulsing streams is represented. The criterion of economic expediency of the system of formation of stream currents is suggested.